Brìgh an Òrain = A story in every song : the songs and tales of Lauchie MacLellan - Shaw, John William; Ornstein, Lisa.; MacLellan, Lauchie, 1910-1991. (Montreal ; Ithaca : McGill-Queen's University Press, 2000)
"A penetrating look at the life and work of a twentieth-century Gaelic singer-storyteller from Nova Scotia, Brigh an Orain - A Story in Every Song situates the inherited art of a fourth-generation Canadian Gael in its biographical, social, and historical contexts. It includes the words, music, and English translations for the songs plus an autobiography told in Lauchie MacLellan's usual entertaining style."--Jacket.
Front Matter -- Contents -- Foreword -- Preface -- Introduction -- Gaelic Singing and Broad Cove Parish -- Air Réir Mo Sgeula -- Na h-Òrain -- Na Sgeulachdan -- Notes -- Sources -- Index
Principally biographical and critical commentary from various sources.
Songs: p. [95]-299.
Includes bibliographical references (pages 419-427) and index.
Songs and tales in Gaelic with English translations; commentary in English.
Print version record.
JSTOR
Keywords: MacLellan, Lauchie, -- 1910-1991 -- Criticism and interpretation; MacLellan, Lauchie, -- 1910-1991; Singers -- Nova Scotia -- Cape Breton Island -- Biography; Folk songs, Scottish Gaelic -- Nova Scotia -- Cape Breton Island; Tales -- Nova Scotia -- Cape Breton Island; Celts -- Nova Scotia -- Cape Breton Island -- Folklore; MacLellan, Lauchie, -- 1910-1991.; Chansons folkloriques gaéliques -- Nouvelle-Écosse -- Cap-Breton, Île du; Contes -- Nouvelle-Écosse -- Cap-Breton, Île du; Celtes -- Nouvelle-Écosse -- Cap-Breton, Île du -- Folklore; Chanteurs -- Nouvelle-Écosse -- Cap-Breton, Île du -- Biographies; Chansons folkloriques écossaises (gaéliques) -- Nouvelle-Écosse -- Cap-Breton, Île du; MUSIC -- Printed Music -- General; MUSIC -- Genres & Styles -- Folk & Traditional; Celts; Folk songs, Scottish Gaelic; Singers; Tales; Nova Scotia -- Cape Breton Island; MacLellan, Lauchie, -- 1910-1991.; Chansons folkloriques gaeliques -- Nouvelle-Ecosse -- Cap-Breton, Ile du; Contes -- Nouvelle-Ecosse -- Cap-Breton, Ile du; Celtes -- Nouvelle-Ecosse -- Cap-Breton, Ile du -- Folklore; Electronic books; Biographies; Criticism, interpretation, etc; Folklore